Kajian Yuridis terhadap S.E Dirjen Pajak No. 3 / P.J / 2011 tentang Pajak Penghasilan Atas Penghasilan Berupa Royalti dan Perbelakuan Pajak Pertambahan Nilai Atas Pemasukan Film Impor di Indonesia - Gusminarti Gusminarti (Universitas Syiah Kuala, 2012)
ABSTRACT: Income tax is a tax levied on income, the meaning of income according to article 4 paragraph 1 of income tax’s constitution enacton in 2009 is any additional economic capability received by the taxpayer either coming from Indonesia and outside Indonesia that could be used for consumption or to increase the wealth of taxpayers concerned with the name and in whatever form as well. While the value added tax is a kind of center that collected taxes done at the time of the transfer of taxable goods and taxable services from one taxpayer to another taxpayer. Related to both these tax law on January 10, 2011 the government through the Directorate General of Taxation issued a Circular Letter Number. 3 / PJ/2011 (SE DGT) on Income Tax Form Income Royalties and Treatment of Value Added Tax on Importation of Films Imports to Indonesia. Issuance of this circular by the government is in order to provide a uniform understanding and application of the Income Tax treatment of Royalty Income and Value Added Tax on imported film entry Indonesia with the DGT S.E No. 3 / PJ / 2011, has received a serious response by Frank. S Rutten Vice President of the Motion Pictures Association (MPA) to Southeast Asian countries rather on Thursday, February 17th, 2011 ago, which immediately gave a statement that the Association of American film producer (Hollywood) will decide the distribution of their films to the country of Indonesia during the government still treats the new tax provisions related to the imposition of uniformity Royalty imported films. So that, we formulate the problem as follows, how the legal position of Director General of Taxes Circular and anything that is applied from both Tax Act above in the Circular Letter. From the results of the discussion concluded that the DGT Circular is a form of regulation of Wisdom (beleid regels) issued by the competent authority for it, and the Director General of Taxes Circular was applied several articles of the Income tax law and tax law value. Juridical Study Towards the Circular of General Directorate of Taxation Department No. 3P.J/2011 regarding Income Tax of The Royalty Income and The Aplication of Additional Tax Value of Imported Film in Indonesia